The dilemmas of tax coordination in the enlarged European Union - Jens Brøchner; Jesper Jensen; Patrik Svensson; Peter Birch Sørensen (Center for Economic Studies and ifo Institute (CESifo), 2006)
This study evaluates the economic effects of corporate tax coordination in the enlarged European Union using a computable general equilibrium model and a comprehensive set of scenarios for both a common corporate EU tax base and for full harmonisation of tax bases and tax rates. Our main findings are as follows: (i) Corporate tax coordination can yield modest aggregate welfare gains, but the details of the coordination policies determine outcomes and economic gains cannot be taken for granted. (ii) All scenarios for coordination leave some EU Member States as winners and others as losers. An agreement on tax coordination is therefore likely to require elaborate compensation mechanisms. (iii) The large and diverse country effects suggest that Enhanced Cooperation for a subset of the Member States may be the most likely route towards tax coordination. Coordination among a subset of relatively homogenous Member States will lead to less radical policy changes, but also to smaller gains. (iv) Identifying winners and losers from coordination for the purpose of a compensation mechanism may be problematic, since countries experiencing gains in GDP and welfare tend to lose tax revenues, and vice versa.
Keywords: H87; H77; 330; Unternehmensbesteuerung; EU-Steuerrecht; Makroökonomischer Einfluss; Allgemeines Gleichgewicht; EU-Staaten